A low-cost flexible piezoresistive sensor with high sensitivity and broad detection range based on porous random microstructures for wearable electronics. (1st February 2023) - Zhang, Yangyang; Zhang, Xiaopeng; Zhang, Xia; Li, Liping
Abstract: Due to their simple structures and high sensitivity, flexible piezoresistive sensors have great potential for physiological monitoring, tactile recognition of prosthetics, and electronic skin. Here, a flexible piezoresistive sensor based on porous random microstructures and having high sensitivity and a wide detection range is proposed. Conductive carbon black was used as an active filler and thermoplastic expandable microspheres and sandpaper were used as templates for the fabrication of the pore structures and random microstructures of the substrates, respectively. Synergistic interactions between these two components in the sensor led to a high sensitivity of 11.02 kPa −1 (0–6 kPa), wide measuring range (0–30 kPa), rapid response time (<200 ms), and long-term durability (>2000 cycles). The sensor was effective for monitoring a variety of hand movements, including bending of the fingers and wrist. In addition, the sensors were effective when attached to a robotic hand to simulate the traditional Chinese medicine pulse diagnosis and to grasp objects. This device thus has broad application prospects in the field of human-machine interactions and robot teleoperation.